Pengaruh Motivasi Dan Disiplin Kerja Terhadap Kinerja Karyawan - Bulan Tati Fitria; Deti Racaliani Hardianti (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2019)
The aim of this study is finding and analyzing the impact of motivation and work discipline on employee performance. This study uses the descriptive analysis and verification analysis with 35 respondents. In addition, this study uses path analysis. The result shows that motivation is adequate, the result of work discipline is acceptable, and employee performance is decent. The direct and indirect effect of motivation on performance is 0,369. The direct and indirect effect of work discipline on performance is 0,362. The entire effect is 0,731. Coefficient determination is 73.1% and the rest is 26.9% from the other variables that have effect on employee performance but they were not analyzed on this study.